Stimulation of germination of Acacia Pulchella: laboratory basis for forest management options - Portlock, C.; Shea, S.; Majer, Jonathan; Bell, D. T. (1990)
(a) The leguminous shrub Acacia pulchella is a valued understorey species of jarrah (Eucalyptus marginata)forests in south-western Australia. It regenerates from buried seeds mainly after fire, which breaks seed dormancy.(2) Experiments examined the effects on germination of five heating durations on A. pulchella seeds buried at five depths in two soil types kept dry or at a field capacity.(3) Mean germination of untreated seeds was only 4%, but germination was >60% after temperatures reached 55-60 deg C, with some seeds germinating after exposure to temperatures >200 deg C.(4) Duration of heating, depth of seed burials, and soil moisture content all affected germination response to soil heating, but sand and gravel soils gave the same response.